2002
DOI: 10.1007/s10350-004-6317-7
|View full text |Cite
|
Sign up to set email alerts
|

A National Strategic Change in Treatment Policy for Rectal Cancer—Implementation of Total Mesorectal Excision as Routine Treatment in Norway. A National Audit

Abstract: A refinement of the surgical resection technique for rectal cancer can be achieved on a national level, the technique of total mesorectal excision can be widely distributed, and surgery alone can give good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
286
4
26

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(328 citation statements)
references
References 21 publications
12
286
4
26
Order By: Relevance
“…The term 'total mesorectal excision' (TME) is often used for this type of surgery, although the entire mesorectum is not always excised in high rectal cancers. Concentration of rectal cancer surgery to a colorectal cancer unit and extensive surgical training programmes have also resulted in low local failure rates (approximately 10 Á/15% after 2 Á/5 years) in unselected Swedish patient populations (3,54) and in Norway (55). Several individual hospitals have also reported low recurrence rates after having introduced the TME concept (e.g.…”
Section: Radiotherapy In Resectable Rectal Cancermentioning
confidence: 99%
“…The term 'total mesorectal excision' (TME) is often used for this type of surgery, although the entire mesorectum is not always excised in high rectal cancers. Concentration of rectal cancer surgery to a colorectal cancer unit and extensive surgical training programmes have also resulted in low local failure rates (approximately 10 Á/15% after 2 Á/5 years) in unselected Swedish patient populations (3,54) and in Norway (55). Several individual hospitals have also reported low recurrence rates after having introduced the TME concept (e.g.…”
Section: Radiotherapy In Resectable Rectal Cancermentioning
confidence: 99%
“…They found that the TME group did better compared to the conventional surgery group with respect to local recurrence rate (6 % vs. 12 %) and 4 year survival rate (73 % vs.60 %) 20 . The current reported local relapse with TME is less than 5 % [18,19]. Apart from a good surgical technique for TME, following a standard histopathology evaluation protocol is equally important as shown by Quirke and Nagtegaal et al [20].…”
Section: A) Mechanical Bowel Preparationmentioning
confidence: 86%
“…has yielded local recurrence rates of 30% or higher [30] . The benefits of the mesorectal dissection technique have been confirmed in several European countries after introduction of training programs and national consensuses of TME as the standard operation method for rectal cancer [11,18,31] . It has been documented that cancers located in the upper rectum do not need to be removed along with all the fatty tissue surrounding the rectum (mesorectum) down to the pelvic floor [32] .…”
Section: Anterior Resectionmentioning
confidence: 99%